2020
DOI: 10.1371/journal.pone.0240678
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of anemia and associated factors among adult diabetic patients in Tertiary Teaching Hospital, Northern Ethiopia, 2019, cross-sectional study

Abstract: Background Patients with Diabetic Mellitus are at higher risk of different complications. Many previous studies show that anemia among diabetic patients is poorly diagnosed. Objective This study aimed to assess the magnitude and associated factors of anemia among adult diabetes patients having regular follow up at the diabetic clinic of Ayder Comprehensive Specialized Hospital, Tigray, 2018/19. Methods This study was conducted the Diabetic clinic of Ayder comprehensive specialized hospital, Tigray regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“… 39 Depending on sample size, two studies have a sample size greater than or equal to 384, 39 , 40 and four studies have a sample size less than 384. 34 , 35 , 38 , 41 Four studies were conducted in the Amhara region, 38 41 one study in the Harari region, 35 and one study in the Tigray region 34 Table 1 ). The common associated factors reported by included studies were glomerular filtration rate, sex, duration of diabetes, and age of diabetic patients ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 Depending on sample size, two studies have a sample size greater than or equal to 384, 39 , 40 and four studies have a sample size less than 384. 34 , 35 , 38 , 41 Four studies were conducted in the Amhara region, 38 41 one study in the Harari region, 35 and one study in the Tigray region 34 Table 1 ). The common associated factors reported by included studies were glomerular filtration rate, sex, duration of diabetes, and age of diabetic patients ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 34,35,38,40 included in the meta-analysis have revealed that there was no difference among male and female diabetic patients on the occurrence of anemia (POR, 95% CI: 1.2 (0.94-1.52)) with a significant level of heterogeneity (I 2 = 89%, p < 0.001; Figure 8).…”
Section: Sex Of Diabetic Patient and Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Three regional states (provinces) of Ethiopia were represented in the studies: six studies were conducted in Amhara, [20][21][22][23][24][25] 1 study in Tigray, 26 and 2 study in Oromo regional state. 27 Six studies [21][22][23][24]26,28 had used a systematic sampling strategy while the other 3 studies 20,27 used a simple random sampling to select their representative sample. The mean age of study participants ranged from 40 to 56.3 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A decrease in the activity of these enzymes leads to oxidative stress and the accumulation of the oxidized denatured Hb forms, which trigger the eryptosis process (so-called quasi-apoptosis of RBC) [143]. It promotes the development of hemolytic anemia [171], the prevalence of which in patients with diabetes mellitus is estimated at 22% [170] or 18% [172]. Oxidative and carbonyl stress promote the oxidation of intracellular GSH, which is consumed in the reactions with antioxidant enzymes and glyoxalase system.…”
Section: Relationship Of Carbonyl Stress With Oxidative and Nitrosatimentioning
confidence: 99%